Frequency and clinical significance of short cervix in patients with preterm premature rupture of membranes - Lee, Seung Mi (PLoS One, 2017)
OBJECTIVE: Cervical length measurement has been uggested as a useful tool for predicting intra-amniotic infection/inflammation in preterm labor, but little information is available in the setting of preterm premature rupture of membranes (pPROM). We aimed to determine whether a short cervical length is independently associated with an increased risk of intra-amniotic infection or inflammation and impending preterm delivery in women with pPROM. METHODS: This was a retrospective cohort study involving 171 consecutive singleton pregnant women with pPROM (21+0–33+6 weeks’ gestation), who underwent amniocentesis. Amniotic fluid (AF) was cultured, and assayed for interleukin (IL)-6 and IL-8. Cervical length was measured at the time of amniocentesis by transvaginal ultrasonography with an aseptic technique. Short cervical length was defined as a cervical length of ≤15 mm. Intra-amniotic infection was defined as a positive AF culture for microorganisms and intra-amniotic inflammation was defined as elevated AF concentrations of IL-6 or IL-8 (IL-6 ≥1.5 ng/mL and/or IL-8 ≥1.3 ng/mL). RESULTS: Fifty (29.2%) women had a sonographic cervical length of ≤15mm. On univariate analysis, short cervical length was associated with an increased risk for intra-amniotic infection and/or inflammation; no other parameters studied showed a significant association. Multivariable analyses indicated that short cervical length was significantly associated with a higher risk of impending preterm delivery (within 2 days of measurement, within 7 days of measurement, and before 34 weeks), and remained significant after adjustment for potential confounders. CONCLUSION: In women with pPROM, short cervical length is associated with an increased risk for intra-amniotic infection/inflammation and associated with impending preterm delivery, independent of the presence of intra-amniotic infection/inflammation.